Does richness lose its luster? Effects of extensive practice on semantic richness in visual word recognition - Hargreaves, Ian S.; Pexman, Penny M. (Frontiers in Human Neuroscience, 2012)
Previous studies have reported facilitatory effects of semantic richness on word recognition (e.g., Yap, Pexman, Wellsby, Hargreaves & Huff, 2012). These effects suggest that word meaning is an important contributor to lexical decision task (LDT) performance, but what are the effects of repeated LDT practice on these semantic contributions? The current study utilized data from the British Lexicon Project in which 78 participants made lexical decision judgments for 28,730 words over 16 hours. We used linear mixed effects to detect practice-driven changes in the explanatory variance accounted for by a set of lexical predictors that included numerous indices of relative semantic richness, including imageability, the number of senses and ARC. Results showed that practice was associated with decreasing effects of predictors such as word frequency and imageability. In contrast, ARC effects were only slightly diminished with repeated practice, and effects of the number of senses and the age of acquisition were unaffected by practice. We interpret our results within a framework in which variables may dynamically influence lexical processing and the post-lexical decision making mechanisms that also contribute to LDT performance.